2018
DOI: 10.21307/pjm-2018-032
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides Produced by Lactobacillus rhamnosus KL 53A and Lactobacillus casei Fyos Affect Their Adhesion to Enterocytes

Abstract: A b s t r a c tProbiotics promote and help to maintain beneficial microbiota composition of the gastrointestinal tract ecosystem and have a positive impact on the host's health. Production of exopolysaccharides is an important feature of probiotic lactobacilli. It increases the chance of their survival in the gastrointestinal tract and promotes adhesion to the epithelium; therefore, exopolysaccharides are important for the process of colonization. Two lactic acid bacteria strains were used in this study: Lacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However, Lactobacillus EPS was found to promote more the biofilm biomass than the cell viability in biofilms, thus it is likely that other mechanisms are also implicated. Some authors reported that L. rhamnosusderived EPS was involved in the adhesion to intestinal cells, suggesting that from lactobacilli can act as adhesins for Lactobacillus and related genera [35]. At the same time, since EPS are one of the main components of the biofilm extracellular matrix, their availability in the medium can enhance the structure of lactobacilli biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…However, Lactobacillus EPS was found to promote more the biofilm biomass than the cell viability in biofilms, thus it is likely that other mechanisms are also implicated. Some authors reported that L. rhamnosusderived EPS was involved in the adhesion to intestinal cells, suggesting that from lactobacilli can act as adhesins for Lactobacillus and related genera [35]. At the same time, since EPS are one of the main components of the biofilm extracellular matrix, their availability in the medium can enhance the structure of lactobacilli biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Exopolysaccharides might facilitate interactions between the bacteria and the intestinal cells, from initial to permanent adhesion mechanisms (Konieczna et al, 2018). For example, Bifidobacterium longum NB667 contains exopolysaccharides found directly involved in their adhesion to human intestinal mucus.…”
Section: Probiotic Colonization On Gastrointestinal Epithelial Cellsmentioning
confidence: 99%
“… 154 Lactobacillus rhamnosus KL 53A and Lactobacillus casei Fyos EPS Enzymatic deglycosylation Changes in the exopolysaccharide structure decreased adhesion efficiency of probiotic on IECs. 155 Lactobacillus acidophilus NCFM SLP homolog PrtX PrtX-deficient strain (gene deletion) Prt-X deficient strain had increased adhesion to mucin and fibronectin. On antigen presenting cells (DCs) it increased induction of IL-6, IL-12 (pro-inflammatory) and IL-10 (anti-inflammatory), but IL-10/IL-12 ratio, (measure of the balance between pro-inflammatory and anti-inflammatory states) was higher.…”
Section: Evidence Of Involvement Of Adhesins In Probiotic Function By...mentioning
confidence: 99%